Synthesis, Characterization and in vitro Antimicrobial, Antioxidant and Anticancer Activity of Random Copolyester Using 1,4-Dithiane-2,5-diol - Kalpana, B.; Nanthini, R. (Asian Journal of Chemistry, 2019)
A random copolyester was prepared by direct melt polycondensation method using 1,4-dithiane-2,5-diol, 1,4-cyclohexane diol and Sebacic acid in the mole ratio 1:1:2 using titanium tetra isopropoxide as catalyst. The synthesized copolyester poly(1,4-dithiane-2,5-diol sebacate–co–1,4-cyclohexane diol sebacate) (PDCSe) was characterized by FT-IR, 1H NMR and 13C NMR to determine the chemical structure, while wide angle XRD, differential scanning spectroscopy and Inherent viscosity were determined to study its physical properties. Further the antioxidant, antimicrobial and anticancer activities of the synthesized copolyester were determined to study its biological property.